A 174 passenger aircraft pylon design and analysis. - Marcos Vinicius Pirrho Loureiro (2006)
The goal of this work is to verify the pylon design of a 174 passenger aircraft. This aircraft was studied by the fourth class of Embraer's Engineer Specialization Program (PEE 4). The engine of this aircraft is located below the wing and its model is GE CFM-56. The fan size was increased in order to reach a higher air passage ratio. This pylon concept presented here was studied and adopted by the group as the better option for this type of airplane. Due to the short time allowable to this study along the program, this dissertation aim to verify the design chosen, analyzing the pylon loads and, using a finite element model, estimate the preliminary dimensions of this structure. For this verification, the loads were studied and applied in the model. The materials considered were aluminum and steel. Titanium was dismissed due to its high cost nowadays. The dimensions of the engine related to the wing could not be changed because they are a design requirement. The analysis showed that the engine position, forward the wing, causes a high load in the front lugs, increasing these lugs dimensions. Besides, the entire pylon had to be reinforced to withstand the reactions of the front lugs. The solution for this issue would be change the engine dimension related to the wing, reducing the moments or change the pylon concept, with the same purpose. Therefore, the conclusion of this project shows that the pylon configuration shown here is not efficient for this type of aircraft.